Event-by-event fluctuations of the mean transverse momentum in 40, 80, and 158 AGeV/c Pb-Au collisions: CERES collaboration - Adamová, Dagmar; Appelshäuser, Harald; Braun-Munzinger, Peter; Damjanović, Sanja; Dietel, Thomas; Dietrich, Lars; Glässel, Peter; Dubitzky, Wilrid; Milošević, Jovan; Richter, Michael; Specht, Hans Joachim; Stachel, Johanna; et al. (Nuclear physics. A, Nuclear and hadronic physics, 2003)
Measurements of event-by-event fluctuations of the mean transverse momentum in PbAu collisions at 40, 80, and 158 AGeV/c are presented. A significant excess of mean pT fluctuations at mid-rapidity is observed over the expectation from statistically independent particle emission. The results are somewhat smaller than recent measurements at RHIC. A possible non-monotonic behavior of the mean pT fluctuations as function of collision energy, which may have indicated that the system has passed the critical point of the QCD phase diagram in the range of μB under investigation, has not been observed. The centrality dependence of mean pT fluctuations in PbAu is consistent with an extrapolation from pp collisions assuming that the non-statistical fluctuations scale with multiplicity. The results are compared to calculations by the rqmd and urqmd event generators.